The Teacher's Ability To Develop Creatif Dialogue In Learning In Elementary School - Mongdong, Romi J.; Lumapow, Harol R.; Kawulur, Arie; Tumurang, Hetty J. (Technium Social Sciences Journal, 2023)
Teaching with a social studies curriculum is perceived as boring and trivial. This public perception requires teachers to make efforts to maximize the learning process with social studies content. The aim of this research is to describe teachers' ability to develop creative dialogue in elementary school learning, as seen from their planning and implementation in the learning process, as well as the factors influencing their ability. This research uses a qualitative descriptive method. The research subjects are students, teachers, and principals from St. Fransiskus Xaverius Catholic Elementary School in Tomohon City, GMIM 6 Elementary School in Tomohon, GMIM 5 Elementary School in Tomohon, and Uluindano Inpres Elementary School in Tomohon. Data collection techniques include observation, interviews, and documentation study, with the researcher as the main instrument. The data analysis technique consists of four stages: categorization and codification, data reduction, data display, and drawing conclusions and verification. The validity of the research data is ensured through triangulation. The level of elementary school teachers' ability in Tomohon City to plan their teaching is not yet in accordance with the characteristics and essence of creative dialogue. Elementary school teachers in Tomohon City are able to initiate creative dialogue but have not been able to sustain and conclude it. The direction and distribution of teacher questions have successfully improved the process of learning creative dialogue, supported by teachers' ability to involve students in determining discussion topics and setting the timing of questions. However, the teachers' response to students' answers does not contribute to the conclusion of the teaching process, as teachers take over the final conclusion from students' answers. The ability of elementary school teachers in Tomohon City to evaluate the process of teaching creative dialogue shows that they are able to control the flow of learning but have not been able to maintain the continuity of the learning process. The influencing factors are academic and non-academic factors